Addressing the Role of Information Technology in Cold Chain Management Efficiency in the World Class Organizations - Hasan Farsijani; Reza Farzipour Saen; Seyed Mohammad Reza Torabi Pour (Journal of Information Technology Management)
Inadequate attention to the products having shelf life limitation leads to form a new branch of Supply Chain (SC) called Cold Chain (CC). Cold Chain Management (CCM) is referred to handle activities related to perishable products. This research investigates the role of Information Technology (IT) in improving the human resource efficiency, planning and logistic in the CC organizations. The number of 115 questionnaires related to three hypotheses has been distributed among experts and managers in charge of CC activities. The questionnaires have been analyzed through SPSS software and the results have approved hypotheses. Finally, future research suggestions have been given.